EKSPRIMENTASI PEMBELAJARAN KOOPERATIF TIPE STAD DAN TPS DENGAN PENDEKATAN CTL PADA MATERI POKOK SISTEM PERSAMAAN LINEAR DUA VARIABEL DITINJAU DARI GAYA BELAJAR SISWA - Zamroni, Zamroni; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objective of research was to find out: (1) which ones having better achievement, the students using TPS (Think Pair Share) learning with CTL approach or STAD (Students Teams Achievement Divisions) cooperative learning model with CTL approach or direct learning, (2) which ones having better learning achievement, the students with kinesthetic or visual or auditory learning style, (3) in each learning style, which ones having better achievement, the students using TPS (Think Pair Share) learning with CTL approach or STAD (Students Teams Achievement Divisions) cooperative learning model with CTL approach or direct learning, and (4) in each learning model, which ones having better learning achievement, the students with kinesthetic or visual or auditory learning style. The population of research was all VIII graders of Public Junior High schools in Bojonegoro Regency consisting of 55 schools. The sample was taken using cluster random sampling. The sample consisted of 304 students divided into experiment I, experiment II, and control groups. The conclusions of research were: (1) TPS CTL learning provided learning achievement better than STAD CTL and direct, but STAD CTL learning provided learning achievement as same as the direct learning did. (2) The students with kinesthetic learning style had learning achievement better than those with visual and auditory learning styles. But, the students with visual and those with auditory learning styles had equal learning achievement. (3) a. In kinesthetic learning style, all learning models provided the same learning achievement. b. In visual learning style, TPS CTL learning provided learning achievement better than STAD CTL. Meanwhile, direct learning provided the learning achievement as same as the TPS CTL and STAD CTL learning models did. c. In auditory learning style, all learning models provided the same learning achievement. (4) a. In TPS CTL learning model, the students with kinesthetic learning style had better achievement than those with auditory learning style. The students with visual learning style had learning achievement equal to those having kinesthetic and auditory learning styles, b. In STAD CTL learning model, the students with kinesthetic learning style had better achievement than those with visual and auditory learning styles. However, the students with visual learning style had learning achievement equal to those with auditory learning style, c. In direct learning, the three learning styles had the equal learning achievement.Keywords:TPS-CTL, STAD-CTL, Learning Style, learning achievement